Effect of a square tunnel on ground acceleration responses during earthquakes - Tan, Reuben Jit Shen (Nanyang Technological University, 2020)
To understand the effects of size and depth of a square tunnel on peak ground acceleration (PGA) during earthquakes, a finite element model was setup in PLAXIS 2D. The soil model built was modelled after soil conditions above the Bukit Timah Granite formation. Data from the 2014 Ferndale California earthquake was obtained to simulate the worst possible earthquake scenario in Singapore. The size and depth of the tunnel was varied during the analyses. A 6.0 m square tunnel was analysed at four different embedment depths, and the PGA results obtained were compared to PGA of the model without tunnel. It was determined that the deeper the embedment depth of a tunnel, the greater the horizontal PGA of the ground surface. The tunnel at depth of 0.8D had resulted in an amplification of almost three times compared to a case with no tunnel. The analysis of the effect of tunnel sizes on PGA was set at a depth of 0.6D. The results showed that the larger the tunnel, the higher the horizontal PGA recorded. The smallest tunnel, 3.0 m, was found to have little effect on the PGA. In contrast, the 12.0 m tunnel amplified PGA by almost five times. For the results obtained from both size and depth, the maximum PGA recorded was not always directly above the tunnel, but some distance away.